Sistem Pakar Penyakit Mata Merah Berbasis Web Menggunakan Metode Decision Tree dengan Forward Chaining - Tri Erna Suharningsih; I Gede Pasek Suta Wijaya; Ario Yudo Husodo (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2019)
This paper presents an expert system disease of the red-eye web-based using the decision tree with forward chaining algorithms. The aims are to design and to implement a web-based expert system of disorders of the red-eye (disease) and to provide a second opinion web tool based for diagnosing the red eye (disease). The system was built using framework CodeIgniter with php and html. The experimental results show that the system has run well which is indicated by valid black box achievements, 55% of conformity to experts from the Faculty of Medicine of the University of Mataram and 4.19 of five leakage scale of MOS parameter. It means that the expert system of the red-eye disease has been work properly and potentially to be implemented for the community.